An experimental study of the influence of loading direction on the thermohydrodynamic behaviour of twin axial groove journal bearing - Arab-Solghar, A. (2011)
An experimental assessment of the influence of the angle between the groove axis and the load line on the thermohydrodynamic behaviour of twin groove hydrodynamic journal bearings has been undertaken. At nine different loading direction angles, the oil–bush interface temperature profiles, oil outlet temperature, maximum bush temperature, total flow rate, and oil flow rate through each groove were measured for variable applied load and oil supply pressure while the feeding temperature was kept constant (40ºC). To the authors’ knowledge, this is the first study of the influence of loading direction on the performance of journal bearing with two axial grooves in which the flow rate was measured in each groove for different working conditions under laminar regime. It was found that the variation of loading direction has a strong effect on the bearing performance. Under some running conditions, negative lubricant flow rate (hot oil reflux) at one groove was detected. This seldom-reported phenomenon was found to affect the bearing performance dramatically. Increasing supply pressure yielded a temperature decrease, especially for high loads, and sometimes prevented the occurrence of hot oil reflux.